THE ROLE OF FEMALE COACHES IN THE SPORT OF KURASH - Nigina Ruziboyeva (Modern American Journals, 2025)
This article explores the role of female coaches in the traditional Uzbek sport of Kurash. While Kurash has historically been dominated by male participants and coaches, the involvement of women as coaches is gradually increasing, revealing new dynamics in the development of athletes and the promotion of gender equality in sports. The paper examines how female coaches contribute not only to the technical training of athletes but also to their psychological and moral development. It also analyzes the challenges they face in a traditionally male-centered environment and discusses policy implications for expanding women's participation in sports leadership.
Keywords: Kurash, female coaches, gender equality in sports, coaching strategies, sports pedagogy, traditional wrestling, women in leadership, athlete development, sport psychology.